Applegarth: Rhetoric in American Anthropology - Huebner, Daniel R. (Serendipities. Journal for the Sociology and History of the Social Sciences, 2016)
Book Review of: Risa Applegarth, Rhetoric in American Anthropology Pittsburgh, PA: University of Pittsburgh Press, 2014 Pp. xii+267 ISBN10: 0822962950 ISBN13: 9780822962953 Price: €28,09